Markov Uniqueness and Rademacher Theorem for Smooth Measures on an Infinite-Dimensional Space under Successful-Filtration Condition - Kulik, A.M. (Український математичний журнал, 2005)
For a smooth measure on an infinite-dimensional space, a “successful-filtration” condition is introduced and the Markov uniqueness and Rademacher theorem for measures satisfying this condition are proved. Some sufficient conditions, such as the well-known Hoegh-Krohn condition, are also considered. Examples demonstrating connections between these conditions and applications to convex measures are given. Для гладкої міри на нескінченновимірному просторі введено умову "успішної фільтрації" та доведено марковську єдиність і теорему Радемахера для мір, що задовольняють цю умову. Розглянуто деякі достатні умови, такі як відома умова Хєег-Крона, наведено приклади, що демонструють зв'язок між цими умовами, та застосування до опуклих мір.